Pengaruh Motivasi Kerja, Disiplin Kerja, dan Lingkungan Kerja Non Fisik Terhadap Kinerja pada CV Bersama Jaya Express Surabaya - Syamziah Budi Haryanti; Sri Budi Kasiyati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
CV Bersama Jaya Express is a company engaged in expedition and goods delivery services, serving both local and inter-island shipments for individual and corporate needs. In its operations, the company heavily relies on the quality of human resources, especially operational and administrative employees who are directly involved in the delivery process, handling of goods, and customer service. This study aims to examine the influence of work motivation, work discipline, and non-physical work environment on employee performance. The research involved 50 respondents using a survey method and questionnaire as the instrument. Data analysis techniques include validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, correlation coefficient, determination coefficient, and hypothesis testing (partial t-test and simultaneous F-test) using SPSS version 26. The results show that work motivation, work discipline, and non-physical work environment each have a positive and significant effect on employee performance, both partially and simultaneously. This research is expected to serve as a consideration in human resource development, especially in optimizing employee performance.